Predictors of Sleep Quality Among Type 2 Diabetes Mellitus Patients - Febriani, Dita Hanna (Jurnal Berita Ilmu Keperawatan, 2024)
One of the health problems experienced by patients with type 2 diabetes mellitus is poor sleep quality. Poor sleep quality is an important factor in poor blood sugar regulation. This study aims to determine the predictors of sleep quality in patients with type 2 diabetes mellitus at a private hospital in Yogyakarta. This research was conducted using a cross sectional approach on 150 type 2 diabetes mellitus patients who were recruited at the Endocrine Clinic at a private hospital in Yogyakarta. The questionnaires used in this research were demographic data questionnaires, Perceived Stress Scale (PSS-10), Pittsburgh Sleep Quality Index (PSQI). Data analysis was carried out using Multiple hierarchical linear regression. The research results show that the average stress score of respondents in this study was 16.13 (SD = 4.59), which is in the medium category. Global PSQI showed that respondents experienced poor sleep quality (mean = 5.33, SD = 1.79). The Perceived Stress Scale score contributed 23.6% to the sleep quality score. The higher the respondent's stress level, the lower the respondent's sleep quality. Nurses can develop interventions to improve the sleep quality of type 2 diabetes mellitus patients.